The Time-Driven Activity-Based Costing Model for a Small Startup in Indonesia - Dewi Fitriasari; Naoko Kawahara (Bina Nusantara University, 2020)
The research proposed a Time-Driven Activity-Based Costing (TDABC) model for cost and human capital analysis in a small startup in Indonesia. TDABC discussed and illustrated the integration of capabilities into cost and performance in startups. The researchers applied a qualitative simulation method. The data were taken from actual regulatory data of wage and salary from the local government of Jakarta. The other data were simulated data based on a software development process for a small startup. The result indicates that the TDABC can assist the company to trace its performance and costs. Additional factors in implementing the costing system are provided for further research and practical considerations in adopting the costing system.